2020
DOI: 10.1038/s41598-020-76699-7
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genomes elucidate diversity, phylogeny, and taxonomy of Pulsatilla (Ranunculaceae)

Abstract: Pulsatilla (Ranunculaceae) consists of about 40 species, and many of them have horticultural and/or medicinal value. However, it is difficult to recognize and identify wild Pulsatilla species. Universal molecular markers have been used to identify these species, but insufficient phylogenetic signal was available. Here, we compared the complete chloroplast genomes of seven Pulsatilla species. The chloroplast genomes of Pulsatilla were very similar and their length ranges from 161,501 to 162,669 bp. Eight highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 69 publications
(102 reference statements)
2
28
0
Order By: Relevance
“…This result as well as those from mVISTA, SSRs, and repeat sequence analyses support that the intergenic spacers harbor the highest levels of variation in plastomes. High variability regions in the intergenic spacer have been reported in other studies and shown excellent discriminating ability, such as Echinacea of Asteraceae , Rhodiola of Crassulaceae (Zhao et al, 2019), and Pulsatilla of Ranunculaceae (Li et al, 2020). Therefore, developing specific barcodes in the intergenic spacers is well-founded and should provide a reliable approach to assess the phylogenetic relationships and identification among Maddenia species.…”
Section: On Specific Barcoding Of Maddeniamentioning
confidence: 80%
“…This result as well as those from mVISTA, SSRs, and repeat sequence analyses support that the intergenic spacers harbor the highest levels of variation in plastomes. High variability regions in the intergenic spacer have been reported in other studies and shown excellent discriminating ability, such as Echinacea of Asteraceae , Rhodiola of Crassulaceae (Zhao et al, 2019), and Pulsatilla of Ranunculaceae (Li et al, 2020). Therefore, developing specific barcodes in the intergenic spacers is well-founded and should provide a reliable approach to assess the phylogenetic relationships and identification among Maddenia species.…”
Section: On Specific Barcoding Of Maddeniamentioning
confidence: 80%
“…Chloroplast (cp) genomes have been widely used to infer plant phylogenetic relationships at all taxonomic levels in angiosperms because of their conserved structure, uniparental inheritance, general lack of recombination, and small effective population size (Cosner et al 2004;Wicke et al 2011). With the rapid development of next-generation sequencing, cp genomes are increasingly being used for phylogenetic relationship reconstruction (Li et al 2020a;Mu et al 2020;Zhao et al 2020;Uckele et al 2021). Since the first oak cp genome for Q. rubra was published in 2014, up to 30 species have been sequenced (Alexander & Woeste 2014;Li et al 2020b;Zhang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although these variations occur in both the gene region and the intergenic region, they were found more in the intergenic region than gene region [42]. In the plastomes of Polygonaceae, the number of genes, as well as the length of gene regions, are mostly similar (Table 2, Fig.…”
Section: Plastome Variationmentioning
confidence: 93%